Chlorhexidine preserves the hybrid layer in vitro after 10-years aging. Issue 5 (May 2020) - Breschi, Lorenzo; Maravic, Tatjana; Comba, Allegra; Cunha, Sandra Ribeiro; Loguercio, Alessandro D.; Reis, Alessandra; Hass, Viviane; Cadenaro, Milena; Mancuso, Edoardo; Mayer-Santos, Eric; Niu, Lina; Pashley, David H.; et al.
Highlights: Endogenous enzymatic activity was lower in CHX-pretreated samples at T0 and T10-yr . 95% of the hybrid layer was preserved in the CHX-pretreated samples after 10 years. CHX is still present in the hybrid layer after 10 years aging in artificial saliva. CHX-pretreatment could improve hybrid layer preservation over time. Abstract: Objective: The present study investigated the ability of a chlorhexidine (CHX)-containing primer (0.2% aqueous solution) to inhibit dentinal enzymes, preserve the hybrid layer (HL) and remain within the HL, after 10 years of aging in artificial saliva at 37 °C. Methods: Non-carious extracted molars were assigned to two groups, cut into slabs exposing middle/deep dentin, etched and bonded with Adper Scotchbond 1XT (SB1XT) with or without 0.2% CHX aqueous solution pretreatment. Composite build-ups were made, and the specimens were cut in 1-mm thick bonded sticks. In situ zymography was performed on freshly prepared specimens (T0 ) and specimens aged for 10 years (T10-yr ) at 37 °C in artificial saliva, to investigate endogenous gelatinolytic activity within the HL. At T10-yr, specimens were also decalcified and embedded in epoxy resin for TEM analysis. Micro-Raman spectroscopy was performed at T0 and T10-yr to evaluate the chemical profiles in intertubular dentin and the HL. Results: In situ zymography showed less pronounced enzymatic activity in the CHX-pretreated group ( p < 0.05) regardless of aging, maintaining a similar level of fluorescence at T0 and T10-yr ( p > 0.05). TEM results showed that 98% of the HL had been degraded in the control group, while 95% of the HL was intact in the experimental group. Moreover, all the Raman spectra peaks assigned to CHX could be identified only in the CHX-pretreated group (T0 and T10-yr ). Significance: In vitro, CHX remains in the HL after 10 years with its inhibitory effect preserved. This may be the underlying factor for HL preservation after this long aging period.